Estimation of Population Density And Food Sort of KELASI (Presbytis Rubicundamuller 1838) in Nyaru Menteng Arboretum of Palangka Raya - Fouad Fauzi; Reni Rahmawati; Penyang Sandan (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
Nyaru Menteng Arboretum is one of Conservation area in Palangka Raya for biodiversity protection width 65,2ha and in that area have established an Orang Utan Reintroduction Center from Borneo Orangutan Save Foundation (BOSF). The aims of this research are to estimated the population density of Kelasi in this area and to know many kinds of Kelasi food and the part of trees that Kelasi put to eat. The result of this research that has found one species (young class) in January 2017, then we can find 3 species again in April 2017 there is one male, one female, and one young kelasi. Population density rate of Kelasiof 2017 is 0,06 species/ha that meaning is population density of Kelasi have a degraded experience if comparing with the same population density data on 2007 that found 15 species in the area (in 2 group)with 0,23 species/ha. Food sort of Kelasi is juvenile of : Jambu-jambu (Syzgium cerinum), Saga (Adenathera microsperma), cassava (Manihot utilisima), rubber (Hevea brasiliensis), pineapple (Ananas comosus), Kelakai (Stenochlaena ralustris) dan jackfruit (Artocarpus integra), other fruits and residue of orangutan food in Reintroduction area lie pineapple and papaya.